Enhancing the performance of poly(3-hexylthiophene)/ZnO nanorod arrays based hybrid solar cells through incorporation of a third component - Que, Wenxiu (2014)
Sparse ZnO nanorod arrays (NRAs) are fabricated on transparent conducting oxide coated glass substrates by using a modified liquid phase epitaxial growth method. By adjusting the polymer concentrations and the spin-coating parameters, full infiltration of poly(3-hexylthiophene) (P3HT) into the as-prepared ZnO NRAs is achieved at 130°C in vacuum. A third component is incorporated into the P3HT/ZnO NRAs ordered bulk heterojunctions (BHJs) either through ZnO surface modification with N719 dye or CdS shell layer or by inclusion of a fullerene derivative into the P3HT matrix. Experimental results indicate that performances of the hybrid solar cells are improved greatly with the incorporation of a third component. However, the working principles of these third components differ from one another, according to morphology, structure, optical property, charge transfer and interfacial properties of the composite structures. An ideal device architecture for hybrid solar cells based on P3HT/ZnO NRAs ordered BHJs is proposed, which can be used as a guidance to further increase the power conversion efficiency of such solar cells.